Palgrave Handbook of Inter-Organizational Relations in World Politics - Biermann, Rafael ; Koops, Joachim A. (Palgrave Macmillan, 2020)
This unique handbook brings together a team of leading scholars and practitioners in order to map, synthesize and assess key perspectives on cooperation and rivalry between regional and global organizations in world politics. For the first time, a variety of inter-disciplinary theoretical and conceptual perspectives are combined in order to assess the nature, processes and outcomes of inter-organizational partnerships and rivalries across major policy areas, such as peace and security, human rights and democratisation as well as finance, development and climate change . This text provides scholars, students and policy-makers of International Relations with an exhaustive reference book for understanding the theoretical and empirical dimensions of an increasingly important topic in International Relations (IR), Global Governance and related disciplines.